2009
DOI: 10.1186/1471-2202-10-35
|View full text |Cite
|
Sign up to set email alerts
|

Electro-acupuncture promotes survival, differentiation of the bone marrow mesenchymal stem cells as well as functional recovery in the spinal cord-transected rats

Abstract: Background: Bone marrow mesenchymal stem cells (MSCs) are one of the potential tools for treatment of the spinal cord injury; however, the survival and differentiation of MSCs in an injured spinal cord still need to be improved. In the present study, we investigated whether Governor Vessel electro-acupuncture (EA) could efficiently promote bone marrow mesenchymal stem cells (MSCs) survival and differentiation, axonal regeneration and finally, functional recovery in the transected spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 69 publications
8
102
0
6
Order By: Relevance
“…However, more work is required before these new mobilization regimes can be introduced into the clinic. Previous studies have reported that EA could promote the survival and homing of transplanted bone marrow MSCs [22]. Our study indicated that EA was a sensitive stimulus for MSC mobilization.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…However, more work is required before these new mobilization regimes can be introduced into the clinic. Previous studies have reported that EA could promote the survival and homing of transplanted bone marrow MSCs [22]. Our study indicated that EA was a sensitive stimulus for MSC mobilization.…”
Section: Discussionsupporting
confidence: 47%
“…In addition, Chen and colleagues reported that electro-acupuncture (EA) improved survival and migration of transplanted neural stem cells in injured rat spinal cord [21]. Another study further showed that the survival and differentiation of transplanted MSCs were promoted by EA treatment [22]. We therefore hypothesized that acupuncture or EA might be an effective stimulus to induce the release of endogenous MSCs into the blood.…”
Section: Electro-acupuncture Promotes Endogenous Multipotential Mesenmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the pathological outcomes of CSCI is demyelination caused by myelin-forming oligodendrocyte death through necrosis and/or apoptosis [2,3]. Electroacupuncture (EA), which originated in ancient China, has been used in wide scope, particularly in neurological diseases, like CNS damage, autonomic nervous system dysfunction, and demyelinating diseases [4][5][6]. However, the therapeutic mechanism remains unclear in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical stimulation can promote the proliferation and differentiation of endogenous neural stem cells and has been reported to enhance the reparative ability of nervous tissue [4,5]. Acusector and electric field treatments have been used for spinal cord injuries in both experimental animals and clinical practice [6][7][8][9]. Jiaji, also termed "Xieji" or "Xiaji," refers to acupuncture points (acupoints) located on either side of the vertebral column.…”
mentioning
confidence: 99%